Character education through poetic inquiry: teaching poetry as a means of moral self-cultivation - Guttesen, Kristian (Journal of poetry therapy, 2025)
This paper offers retrospective reflections following on from a poetry-based character-education intervention, conducted in an Icelandic secondary-school setting. The object of the intervention was to assess the use of poetry in the classroom to enhance students' virtue literacy. This paper discusses the theoretical frameworks undergirding this research project. It assesses Linda Christensen's poetic inquiry as a means of moral self-cultivation. It then compares this approach to the framework of Aristotelian character education. Subsequently, this paper introduces samples of poetic inquiry, namely Gina Edghill's "The Culture of My Community Revealed. Poetic and Narrative Beginnings" and Jacquie Kidd's "White Skin, Brown Soul. A Poetic Autoethnograpy", to show how poetry in the classroom can encourage the development of virtue. More specifically, the paper makes use of the components in a recent Aristotelian phronesis model (APM) to illustrate comparisons of poetic inquiry with Aristotelian character education.